Análise da aplicação da norma de procedimento técnico n° 020 do corpo de bombeiros do estado do Paraná - Teixeira, Renan Kohler (2016)
The high number of claims led government agencies to seek ways to prevent, especially the Fire Department in 2011, changed your security code that was established since 2001, creating "Security Code Fire and Panic" more 40 (forty) regulations, exploring the most diverse area of risk, and enabling more effective prevention. Within the code is the standard procedure Technical 020, which aims to put the building in accordance with emergency signs. These signals help in identifying prevention materials, internal escape routes, as well as alert and ban of possible risks. This work aims to present TPN 020 with respect to type, size, material and application thereof, with the help of practical work carried out in various occupations. The methodology provides an analysis of the norm, highlighting specific points that could be improved, if the theory is transcribed in practice, and present photos of practical work applied to buildings, resulting in a possible improvement program in the standard that makes fire and professional walk following the same application line in order to raise awareness of the importance of prevention.